A novel regulatory circuit between p53 and GFI1 controls induction of apoptosis in T cells - Vadnais, Charles (Sci Rep, 2019)
Here we demonstrate a mode of reciprocal regulation between GFI1 and p53 that controls the induction of apoptosis in T cells. We show that GFI1 prevents induction of p53 dependent apoptosis by recruiting LSD1 to p53, which leads to the demethylation of its C-terminal domain. This is accompanied by a decrease of the acetylation of lysine 117 within the core domain of the murine p53 protein, which is required for transcriptional induction of apoptosis. Our results support a model in which the effect of GFI1’s regulation of methylation at the c-terminus of p53 is ultimately mediated through control of acetylation at lysine 117 of p53. We propose that GFI1 acts prior to the occurrence of DNA damage to affect the post-translational modification state and limit the subsequent activation of p53. Once activated, p53 then transcriptionally activates GFI1, presumably in order to re-establish the homeostatic balance of p53 activity. These findings have implications for the activity level of p53 in various disease contexts where levels of GFI1 are either increased or decreased.